A mulher negra na primeira pessoa: uma construção de raça e gênero nas novelas protagonizadas por Taís Araújo - Oliveira, Laila Thaíse Batista de (2016)
This dissertation aims to understand how the soup opera, as the most popular audiovisual serial narrative in the country, contributes for the construction of race and gender as categories which involve power relations, and analyze how the black woman is represented in those productions through the protagonist characters interpreted by Taís Bianca Gama Araújo Ramos in the global soup operas carefully selected - Da Cor do Pecado, Cobras e Lagartos, Cheias de Charme, Viver a Vida and Geração Brasil. The study is divided in two stages, the first part focuses on presenting the black woman trajectory in Brazilian society, considering socioeconomic aspects, going through the organization of the black population as social movement. It also aims to discuss media, the soup opera and its techniques, bringing up considerations about social representation in media and reflecting in which level it contributes for identity formations of black women in society. In a second stage, we have focused on the empiric research. Therefore, a corpus has been selected composed by scenes from the different phases of the soup operas we have mentioned before, where the protagonist is presented or referred and, furthermore, where it is problematized themes which involve gender and race as pillars of discussion. To reach the goals we have proposed, it will be applied the methodologic procedure presented by Diana Rose (2002), named Analysis of Moving Images. Though the analytic and theoretical path, it is possible to conclude that despite the protagonism of the black woman in those narratives, some representations contribute to stigmatize her image, with negative social impacts. Moreover, the main issues addressed in those productions are relevant for the life of black women, in general, fulfilling an important role in mediating the debate about some social problems. Although, we have observed that the problematic is dealt in a superficial and uncritical way.